Islamic Studies and Local Wisdom at PTKIN in Central Java: Opportunities, Challenges, and Prospects of Pioneering Religious Moderation in Indonesia - Abdurrohman Kasdi; Umma Farida; Choirul Mahfud (Jurnal Hikmatuna, 2020)
This article aims to examine the model of Islamic studies and local wisdom in Islamic State Universities (PTKIN) in Central Java. The method used is qualitative with the sociology of religion approach and belongs to the category of policy research, which is expected to help in recommending effective and efficient policies. The results of this study show that: first, the values ​​of Islamic studies and local wisdom enter into the course at PTKIN, developed through the academic community activities and entered into the structure of Islamic Higher Education, even though using different nomenclature. This study of Islam and local wisdom includes cultural and Islamic acculturation, cultural studies of the Grebeg Besar, Dandangan, Sekaten and other cultures that also have an Islamic spirit. Second, Islamic values ​​and local wisdom developed by the Islamic State Universities in Central Java can sow religious moderation. This can be proven from the ideas, thoughts, and attitudes of the academic community in accepting the differences and heterogeneity of various religious discourses in Indonesia.